The Impact Of Social Media Marketing On Sales Performance Of Small Online Business - Sufian, Atirah; Chin, See Min; Ahmad Murad, Murzidah; Abdul Aziz, Nor Azah (Ubiquity Press, 2020)
This research discusses the factors impacting the use of social media marketing on sales of the online small businesses in Malacca. The primary data was collected by using explanatory survey. The sample consists of 150 respondents who are online small business owners and who had experiences or non-experiences by implementing the social media marketing on their business in Malacca. The requirement analysis test used are pilot test, Reliability Analysis, Validity Analysis, Descriptive Statistic Analysis, Pearson’s Correlation Analysis, Multiple Regression Analysis and Hypothesis Test Analysis. The data analysis technique is used Statistical Package for Social Sciences (SPSS) Version 25.0 software. There are four independent variables such as customers’ feedbacks, communication, content sharing and customers’ relationships will be measured to examine their influence on sales performance of the online small businesses. The research results show that customers’ feedbacks has no direct influence on sales performance, communication has directly influence on sales performance, content sharing has no direct influence on sales performance and customers’ relationships has directly influence on sales performance of online small businesses in Malacca. In overall, the customers’ relationships has been proved to be the most significant factor that impacting the use of social media marketing on sales of the online small businesses because fostering relationships helps the online small businesses to build a positive rapport with customers within the community. The good customers’ relationships will make customers to have a good impression for the business owners and willing to repurchase the products. The achievement of this results could be a reference which offered the knowledge of sales performance on online small businesses for academic purpose, business study or other fields.